2006
DOI: 10.1111/j.1439-037x.2006.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application of Elicitors on Red Clover Isoflavone Content

Abstract: Red clover (Trifolium pratense L.) contains high concentrations of isoflavones, compounds that have received much interest lately due to their presumed benefits for human health. In this experiment we tested the possibility to induce isoflavone production in the foliage of two greenhouse-grown red clover cultivars (ÔAzurÕ and ÔStartÕ) through the application of elicitor compounds. Foliar applications of different concentrations of acetic acid (50, 100, 250 and 500 mm), yeast extract (1, 2, 3 and 4 g l )1 ), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been shown that the concentration of specific elicitors has variable effects on isoflavones in different plant species. The responses of soybean and L. luteus were highly concentration dependent (10,13), but the concentration of elicitors had little effect on red clover (Trifolium pratense L.) (27). It has been suggested that multiple applications of elicitor may be more efficient in enhancing the plant defense response and in simulating isoflavone systhesis (27).…”
Section: Mean Effects Of Elicitor Treatment Variables On Isoflavones ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the concentration of specific elicitors has variable effects on isoflavones in different plant species. The responses of soybean and L. luteus were highly concentration dependent (10,13), but the concentration of elicitors had little effect on red clover (Trifolium pratense L.) (27). It has been suggested that multiple applications of elicitor may be more efficient in enhancing the plant defense response and in simulating isoflavone systhesis (27).…”
Section: Mean Effects Of Elicitor Treatment Variables On Isoflavones ...mentioning
confidence: 99%
“…The responses of soybean and L. luteus were highly concentration dependent (10,13), but the concentration of elicitors had little effect on red clover (Trifolium pratense L.) (27). It has been suggested that multiple applications of elicitor may be more efficient in enhancing the plant defense response and in simulating isoflavone systhesis (27). Like elicitor type and concentration, application time had a significant effect on glycitein and aglycone content but not on other isoflavone components.…”
Section: Mean Effects Of Elicitor Treatment Variables On Isoflavones ...mentioning
confidence: 99%
“…Merr.) and red clover (Trifolium pratense L.) , as well as phenolics in black chokeberry [Aronia melanocarpa (Michx) Elliot] , , black currant (Ribes nigrum L.) , nettle (Urtica dioica L.), dandelion (Taraxacum officinale), and purple coneflower (Echinacea purpurea L. Moench.)…”
Section: Introductionmentioning
confidence: 99%